A duração do vazio: um estudo da prosa poética de Hilda Hilst, de 1970 a 1986 - Vieira, Maria Andrade (2024)
This research seeks to explore the modes of production of emptiness that participate in the support of Hilda Hilst's prose work, in a time frame of creation and editorial launch from 1970 to 1986. The research aims to identify and analyze how the composition of sensations and emptiness sustains the great image that forms the constitution of the three novels in the book. After mapping the blocks of sensation and pockets of emptiness of Hilst's syntax, we analyze the images that form from this threshold. We consider that the game of order and chaos is constantly re-presented and rearranged by Hilstian language, while the rhythm operates in blocks of intensities that take over the body of the text and invite the reader's eyes to move as well. To this end, we dialogue with the concept of emptiness presented by François Cheng and researched by Gilles Deleuze, Félix Guattari, and Ana Godinho Gil